PROFESSIONAL ACTIVITY OF THE ARTIST- TEACHER OF THE NATIONAL SCHOOL (EARLY XXI CENTURY) IN THE CONTEXT OF MODERN TRENDS OF SOCIAL DEVELOPMENT (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to finding out of main tasks of teacher of Ukrainian school in the context of scientific and social reference points, which most economically developed countries develop in obedience to. Among such principles an author considers conducting the necessity of awareness by everybody o f itself as parts of social and natural environment and analysis of the action as such, which influences on the state of all surroundings and concrete personality separately. The fragment of method of forming of similar options at students and students on the example of teaching of cycle of graphic disciplines is examined.